The summer I saved the world-- in 65 days - Hurwitz, Michele Weber (Wendy Lamb Books, 2014)
Inspired by her late grandmother, thirteen-year-old Nina spends a summer secretly doing good deeds for her neighbors and enjoying the changes she brings about, even as she is dealing with changing friendships and family issues.